Medical staff training system development in the Republic of Kazakhstan (1990s) - G.F. Galina (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper considers the issue of providing qualified medical specialists as one of the key problems of the public healthcare system in post-Soviet Kazakhstan. The main activities for medical staff training in the context of the process of development of the public healthcare system in Kazakhstan after the collapse of the Soviet Union have been analyzed. The potential of medical staff of the country during the transition period has been described. The signs of poor education and qualification of medical specialists, regional and professional imbalances in medicine have been revealed. The obtained data demonstrate the major drawbacks of the staff policy in the field of medical education and healthcare organization as a result of the insufficient funding and the command-administrative Soviet system. The main activities for creating the proper conditions for development of the medical staff training system have been discussed in relation with the processes of integration and development of science, education, and public healthcare under the new socio-economic and political conditions. The factors that hinder the development of the effective medical staff training system have been identified, and its main results have been analyzed. The influence of social, economic, moral and cultural factors on the labor market and medical education has been determined. The main stages and key directions in the development of medical staff training have been revealed taking into account the global trends in public healthcare and medical education. It has been established that state measures in the area of reforms in the public healthcare system and medical education have allowed to gradually develop a staff policy for training of medical specialists since the late 1990s. It has been emphasized that the staff policy as a subject of research of the public healthcare institution during the difficult period of establishment of a market economy following the disintegration of the Soviet state makes it possible to identify the important aspects of the social history of the Republic of Kazakhstan.